Community involvement in the development of an environmental education programme: the Tswaing meteorite crater conservation area as a case study - C.H. Swanepoel; C.P. Loubsser; E.M.J.C. Schaller (Koedoe, 2004)
A key requirement for the relevance of applied research in education is its actual impact on society. A case study was undertaken to determine how research insights could be implemented by involving a local community in the design and implementation of environmental education programmes in their environment. The Tswaing Meteorite Crater conservation area project was undertaken with the active participation of teachers, learners and education officers from the communities living around Tswaing, as well as subject specialists. Issues which should be considered in the development of similar programmes were also highlighted.